Phylogeography of Dictyota fasciola and Dictyota mediterranea (Dictyotales, Phaeophyceae): unexpected patterns on the Atlantic-Mediterranean marine transition and taxonomic implications - Daniel Vitales; Joana Aragay; Teresa Garnatje; Amelia Gómez Garreta; Jordi Rull Lluch (PeerJ, 2019)
The Atlantic-Mediterranean marine transition is a fascinating biogeographic region, but still very poorly studied from the point of view of seaweed phylogeography. Dictyota fasciola and D. mediterranea (Dictyotales, Phaeophyceae) are two currently recognized sister species that share a large part of their distribution along the Mediterranean Sea and the Atlantic Ocean, representing a unique study model to understand the diversification processes experienced by macroalgae during and after Messinian at this marine region. In this study, we sampled 102 individuals of D. fasciola and D. mediterranea from 32 localities along their distribution range and sequenced the mitochondrial cox1 and the chloroplast rbcL-rbcS DNA regions for all the samples. Our data do not support the occurrence of two sister species but a morphologically variable and highly genetic diverse species or a complex of species. Most of the observed genetic diversity corresponds to the Mediterranean populations, whereas the Atlantic ones are much more homogeneous. The early-diverged lineages inferred from both mtDNA and cpDNA phylogenetic reconstructions were constituted by samples from the Mediterranean Sea. Together, these results suggest that the Mediterranean Sea acted as a refugium for the D. fasciola–D. mediterranea lineage during the geologic and climatic changes occurred on the region since the Miocene, subsequently dispersing to the Atlantic Ocean.